Mangiferin, a Dietary Xanthone Protects Against Mercury-Induced Toxicity in HepG2 Cells - Agarwala, Sobhika (2010)
Mercury is one of the noxious heavy metal environmental toxicants and is a cause of concern for human exposure. Mangiferin (MGN), a glucosylxanthone found in Mangifera indica, reported to have a wide range of pharmacological properties. The objective of this study was to evaluate the cytoprotective potential of MGN, against mercury chloride (HgCl(2)) induced toxicity in HepG2 cell line. The cytoprotective effect of MGN on HgCl(2) induced toxicity was assessed by colony formation assay, while antiapoptotic effect by fluorescence microscopy, flow cytometric DNA analysis, and DNA fragmentation pattern assays. Further, the cytoprotective effect of MGN against HgCl(2) toxicity was assessed by using biochemical parameters like reduced glutathione (GSH), glutathione-S-transferase (GST), superoxide dismutase (SOD), catalase (CAT) by spectrophotometrically, mitochondrial membrane potential by flowcytometry and the changes in reactive oxygen species levels by DCFH-DA spectrofluoremetric analysis. A significant increase in the surviving fraction was observed with 50 µM of MGN administered two hours prior to various concentrations of HgCl(2). Further, pretreatment of MGN significantly decreased the percentage of HgCl(2) induced apoptotic cells. Similarly, the levels of ROS generated by the HgCl(2) treatment were inhibited significantly (P < 0.01) by MGN. MGN also significantly (P < 0.01) inhibited the HgCl(2) induced decrease in GSH, GST, SOD, and CAT levels at all the post incubation intervals. Our study demonstrated the cytoprotective potential of MGN, which may be attributed to quenching of the ROS generated in the cells due to oxidative stress induced by HgCl(2), restoration of mitochondrial membrane potential and normalization of cellular antioxidant levels.